FENOMENA MURAL SEBAGAI PEMBENTUKAN SUASANA INTERIOR CAFE RESTO - Gerry Rachmat; Riana Safitri (Jurusan Seni Rupa ISBI Bandung, 2019)
The atmosphere of the interior of an accomplishment the concept is based on the theme and the force that want to be made present designer into the space from the results of the idea. The theme and the style has been successfully when the user feel comfortable in space as planned. One of the elements in the form of the interior is through estetik as backdrop, murals painting, painting or plant the interior. Murals is how to draw or media painting on the wall, the wall or surface area that permanent. In contrast to graffiti that focuses more on the content of a writing and made with spray paint so of murals greater freedom to and can get the use media paint the wall or paint wood even paint or dye anything that could be producing images.Keywords: Interior Atmosphere, Mural___________________________________________________________________ Suasana interior adalah sebuah pencapaian konsep yang berbasis pada tema dan gaya yang ingin dihadirkan perancang ke dalam ruang dari hasil gagasan/ ide. Tema dan gaya tersebut berhasil ketika pengguna merasa nyaman dalam ruang seperti yang direncanakan. Salah satu pembentuk suasana interior adalah melalui elemen estetik seperti backdrop, mural, lukisan atau tanaman interior. Mural adalah cara menggambar atau melukis pada media dinding, tembok atau permukaan luas yang bersifat permanen. Berbeda dengan grafiti yang lebih menekankan pada isi tulisan dan dibuat dengan cat semprot maka mural lebih bebas dan dapat menggunakan media cat tembok atau cat kayu bahkan cat atau pewarna apapun yang dapat menghasilkan gambar.Kata Kunci: Suasana Interior, Mural